INCREASED MYOPIA PREVALENCE IN YOUNGSTERS AS A RESULT OF ONLINE LEARNING - Tirayoh, Nicholas Chally; Dja'far, Veri Hardinansyah (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2021)
Myopia is a condition in which distant objects cannot be clearly displayed on the retina by the optical system of the eye, because the incoming light is refracted in front of the retina or yellow spot. Along with genetic factors, another important aspect that affect myopia is lifestyle. When a pandemic strikes, it alters people's behavior. Outdoor activities have decreased significantly, while the use of gadgets has increased as a result of youngsters learning online, which needs the use of gadgets. This study aims to determine the increase in the incidence of myopia in children due the online learning process. The type of research conducted is in the form of literature review. Searches for data that meets literature reviews that match the topic are conducted online. Online searches conducted through scientific journal sites have a diverse and quality database, namely PubMed, Schocar, and Libgen published in the last 6 years (2015-2021). Researchers found 8 journals using keywords relevant to the study. The findings highlight that the use of smartphones can cause DED, myopia and blurred vision. Due the pandemic Covid-19 situation that occur today requires children to take part in online learning programs from home via smartphone screens. Indirectly, short distance activities and lack of exposure to natural sunlight increase asthenopia conditions and increase myopia cases for children. If not addressed early on, these risks becoming an explosion of myopia cases, while the end of the COVID-19 pandemic is still unknown. Therefore, myopia preventive measures are required during pandemic outbreaks that are relevant and effective.